Treating benign paroxysmal positional vertigo of the lateral semicircular canal with a shortened forced position - Giannoni, Beatrice; Pecci, Rudi; Pollastri, Federica; Mininni, Sebastiano; Licci, Giuseppe; Santimone, Rossana; Di Giustino, Fabio; Mandalà, Marco (Frontiers in Neurology, 2023)
Benign paroxysmal positional vertigo (BPPV) is the peripheral vestibular disorder that is most frequently encountered in routine neuro-otological practice. Among the three semicircular canals, the lateral semicircular canal (LSC) is the second most frequently interested in the pathological process. In most cases, LSC BPPV is attributable to a canalithiasis or cupulolithiasis mechanism. The clinical picture of LSC BPPV is that of positional nystagmus and vertigo evoked by turning the head from the supine to the side lateral position. With such a movement, a horizontal positional (and often also paroxysmal) direction-changing nystagmus is generated. Depending on whether the pathogenetic mechanism is that of canalithiasis or cupulolithiasis and depending on where the dense particles are located, LSC BPPV direction-changing positional nystagmus is geotropic or apogeotropic on both lateral sides. Due to its mechanical nature, BPPV is effectively treated by means of physical therapy. In the case of a LSC BPPV, one of the most effective therapies is the forced prolonged position (FPP), in which the patient is invited to lie for 12 h on the lateral side on which vertigo and nystagmus are less intense, to move the canaliths out from the canal (or to shift them inside of the canal from one tract to another) exploiting the force of gravity. Despite its efficacy, FPP is not always well tolerated by every patient, and it cannot be done during the diagnostic session because of its duration. The present study aimed to verify the efficacy of a different forced position, shortened forced position (SFP), with respect to the original FPP. SFP treatment would allow patients to more easily bear the forced position and physicians to control the outcome almost immediately, possibly enabling them to dismiss patients without vertigo. After 1 h of lying on the side where vertigo and nystagmus are the less intense, 38 out of 53 (71.7%) patients treated with SFP were either healed or improved. Although the outcomes are not as satisfying as those of the original FPP, SFP should be considered as a therapeutic prospect, especially by those physicians who work in collaboration with emergency departments or otherwise encounter acute patients to cure them of vertigo as soon as possible.